Training process in rhythmic gymnastics using clubs - Hormez , Samira Zaya; Novikova, L.A.; Mihalina, G.M. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop and introduce into the educational and training process a methodology based on the principles of sensory integration, strict rhythmic organization and variability of exercise conditions, which makes it possible to improve the quality of performing small club throws among gymnasts aged 10-11 years. Methods and structure of the study. A 12-week pedagogical experiment was conducted at the Prestige Rhythmic Gymnastics Center. The study involved 30 gymnasts of the training stage of training, who, taking into account the initial level of technical readiness, age and athletic experience, were divided into two representative groups: control (CG, n=15) and experimental (EG, n=15). A detailed analysis of the requirements for the execution of throwing elements with maces has been carried out, key factors contributing to the occurrence of errors have been identified. Results and conclusions. The developed methodology for improving the technique of small club throws among gymnasts aged 10-11 years at the training stage consists of five target blocks aimed at developing kinesthetic control, rhythmic abilities, proprioception, dynamic balance and technical accuracy. The results of a 12-week pedagogical experiment confirmed the high effectiveness of the developed methodology. In the experimental group, a statistically significant (p<0.05) decrease in allowances for technical errors was recorded.